Representações do imaginário na ficção científica como despertadores de reflexões políticas em “O dia em que a terra parou” de Robert Wise - Guimarães, Márcio Henrique (2015)
To reaffirm the importance of the relationship history-Cinema by analyzing the film "The Day the Earth Stood Still" 1951 work directed by Robert Wise, starting from the defense that the imaginary and reality are intertwined to give life to the central idea your script, which is the use of science fiction as critical discussion tool of camouflaged form politics, American society at a time of great historical tension, outlined the growth of the Cold War and the rise of McCarthyism in the political landscape of United States. We intend with this work, not the exaltation but the recognition of this work as a powerful creative force, building materials discussing issues, political ideas and the historical moment in which the work was conceived. To support such a claim in the office of the historian's relationship with the filmic sources, highlighting the onset of construction of historical thinking.